Surface-Layer Circulations in Suruga Bay Induced by Intrusions of Kuroshio Branch Water - Toyoda, Takahiro; Sakamoto, Kei; Usui, Norihisa; Hirose, Nariaki; Tanaka, Kiyoshi; Katsumata, Takaaki; Takahashi, Daisuke; Niki, Masato; Kutsuwada, Kunio; Miyama, Toru; Nakano, Hideyuki; Urakawa, L. Shogo; et al. (Frontiers in Marine Science, 2021)
The water mass structure in Suruga Bay is strongly influenced by open-ocean water. In particular, it is suggested that intermittent intrusions of the Kuroshio water generate characteristic circulations in the surface layer of the bay. In this study, we investigated the processes of the intrusions of open-ocean water into the bay and related generation of bay-scale cyclonic and anti-cyclonic circulation patterns. In doing so, we used an ocean simulation product with observational data constraint on meso and larger scales and with a resolution fine enough to resolve the smaller-scale intrusion structure. Cyclonic and anti-cyclonic circulation patterns as suggested by previous observational studies were detected as positive and negative first leading empirical orthogonal function (EOF) modes of the velocity field in Suruga Bay. The time scale of occurrences of these patterns was estimated as about 1 month, which was consistent with short-term Kuroshio fluctuations as reported in previous studies. Conditions favorable for generating these patterns were analyzed for three typical Kuroshio path periods individually. As suggested by previous studies, relatively strong northward flow to the west of Zeni-su generally promoted the open-ocean water intrusions into the eastern bay mouth, leading the cyclonic circulation in Suruga Bay. Our results showed that the correlation of this relation was significant for each Kuroshio path period. The open-ocean water intrusion increased the surface-layer temperature in Suruga Bay by about 0.7°C on average. On the other hand, the anti-cyclonic circulation pattern in Suruga Bay tended to be generated with relatively weak northward flow to the west of Zeni-su during the large meander Kuroshio path period, whereas this relation was rather weak during other periods. These results were mostly supported by available observations and would be useful for integrating our understanding of the influences of the western boundary current fluctuations on the circulation and temperature variations in proximal bays.